Host Companies Feedback on the Virtual Internship Performance of International Travel and Tourism Management Students - Felicen, Sevillia; Mejia, Ryan (JPAIR Multidisciplinary Research, 2025)
Internship programs in higher education aim to help students integrate into the corporate world by exposing them to real work environments. This study evaluated host companies' feedback on the performance of Travel and Tourism Management students in virtual internships. It specifically looked at intern profiles, host company feedback on knowledge and skills, self-management, interpersonal skills, attitude, and output, and analyzed differences in feedback based on intern profiles. Descriptive research was used, with 392 interns as subjects. These students participated in virtual internships from the second semester of 2020-2021 to the second semester of 2021-2022. The university's evaluation form served as the assessment tool. Statistical tests included frequency, percentage, weighted mean, rank, Shapiro-Wilk Test, and Kruskal-Wallis. Results showed that most respondents were second-year students in Food and Beverage Services. Host companies reported that interns effectively applied their academic knowledge, maintained proper grooming, cooperated well with supervisors, and submitted tasks accurately and on time. Significant differences were found in feedback regarding knowledge and skills based on semester, year level, and program enrolled.
Keywords: Host Company Feedback; Virtual Internship; Descriptive Design; Philippines